Victoria Sets Up Taskforce To Tackle Harassment Of Women At Gigs (Tone Deaf, 2015)
Following a meeting of the Victorian Live Music Roundtable yesterday, Victorian Minister for Consumer Affairs, Gaming and Liquor Regulation Jane Garrett